Improving the delivery and management of public assistance to the target groups of the Sarawak State Social Welfare Department, through action research - Edward, Kendy (1998)
The delivery and management of public assistance to the target groups of the Sarawak State Social Welfare Department has been identified as a real problem that existed in the department. The problem is evident from the complaint letters from the public, audit queries and the high number of outstanding public assistance cases which had not been investigated as at the end of the year. This study therefore attempted to investigate ways of improving the delivery and management of public assistance to the target groups of the Sarawak State Social Welfare Department, through action research. For the purpose of this study, an action research group comprising 8 officers from the department including the researcher had been formed to take part in the research process in addressing the problem. Besides, 37 field officers involving Asst. Social Welfare officers and Social Welfare Assistants were given a set of questionnaires in the survey regarding the delivery and management of public assistance cases. An interview was also carried out with 26 public assistance recipients from Kuching and Samarahan Divisions to find out about their problems faced with regards to their application, investigation and payment of their public assistance.